On estimates of a fractional counterpart of the logarithmic derivative of a meromorphic function - I. E. Chyzhykov; N. S. Semochko (Математичні Студії, 2013)
We consider the problem of finding lower bounds for growth of solutions of a fractional differential equation in the complex plane. We estimate a fractional integral of the logarithmic derivative of a meromorphic function.